Development of Modern Railway Bogie for Broad Track Gauge - Bogie Frame Assessment - Šťastniak, Pavol; Smetanka, Lukáš; Moravčík, Marián (Manufacturing Technology Journal, 2017)
This article is belonging to the publication series, which we published in the previous issues of this journal and there are described the most important and innovative research and development design solutions and computational procedures as part of European structural funds project. The main object of article is the strength test of new design of freight bogie frame through FEM analysis. For the calculation of the analyzed parts of the bogie through finite element the program ANSYS was used. Results of calculations prove, that new designed construction of the bogie frame satisfies strength conditions.
Keywords: Stress Analysis; Bogie Frame Verification; Computer Tools